Chronic macrocheilia: a clinico‐etiological series of 47 cases. (3rd June 2021) - Toumi, Asma; Litaiem, Noureddine; Gara, Soumaya; Chabchoub, Ines; Bacha, Takwa; Slouma, Maroua; Ben Hassine, Lamia; Rammeh, Soumaya; Jones, Meriem; Zeglaoui, Faten
Abstract: Background: Macrocheilia is an inflammatory disfiguring condition responsible for the swelling of the lips. This multi‐etiological entity represents a diagnostic and therapeutic challenge. Published data on macrocheilia is scarce, often limited to granulomatous cheilitis. Methods: We conducted a retrospective study, including all patients presenting with chronic macrocheilia (CM) for nineteen years. CM was defined as a persistent enlargement of one or both lips for at least eight weeks. Both descriptive and analytical analyses were performed. Results: Of the 47 patients identified, 20 (43%) had cutaneous leishmaniasis, 10 (21%) had Miescher's cheilitis, five (11%) had Melkersson–Rosenthal syndrome, five (11%) had sarcoidosis, one (2%) had lepromatous leprosy, one (2%) had systemic amyloidosis, and one (2%) had Crohn's disease. In four cases, the CM was unlabeled. Ulcerations were significantly associated with leishmaniasis ( P < 0.05). Histological study showed a granulomatous infiltrate in 72% of cases. Medical treatment was adapted to the etiology of CM. Surgery was performed in two cases. Improvement of CM secondary to leishmaniasis was seen in all cases. In patients with idiopathic orofacial granulomatosis, partial improvement was noted in four cases and a total improvement in one case. Recurrences were noted in three cases after complete regression. Conclusions: Macrocheilia is a rare and disfiguring condition that requires an etiological investigation, considering that it can reveal a serious underlying systemic disease. We identified several factors that could help recognize the cause of CM, including age, history of intermittent swelling, the extent of lip enlargement, the existence of ulceration, and systemic symptoms.